“Application of Project-Based Learning in Teaching Fine Arts at Higher Education” - Kodirov Obid Esonboy o‘g‘li (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the scientific and methodological foundations of applying project-based learning in fine arts courses at higher education institutions. The study analyzes methods for developing students’ aesthetic literacy, creative thinking, and critical thinking through project-based analysis and practical artistic assignments. The article also presents pedagogical recommendations to increase students’ engagement and motivation in understanding and creating art.